How to hire employees effectively - Chuel Min, Ju; Kleiner, Brian H (Management research news, 2001)
Provides a framework for effective hiring. Considers job descriptions and personnel specification before outlining ways to attract candidates. Recommends an analysis of recruitment strengths and weaknesses. Touches upon subjects such as the source of candidates, advertising, agencies and selection. Gives different interviewing strategies.